(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Molecular techniques, including denaturing gradient gel electrophoresis (DGGE), 16S rRNA genes clone library construction and metagenomic analysis, were used to describe the bacterial composition of the Karvachar geothermal spring. It was shown the predominance of bacteria belonging to the phyla Proteobacteria, Bacteroidetes, Firmicutes and Cyanobacteria in the studied spring. Representatives of phylum Firmicutes were not detected in the clone library, while DGGE profiling and metagenome analysis confirmed the presence of Firmicutes as one of the major components in the bacterial community.